Medical assistance to aged patients - de Siqueira, José Eduardo (O Mundo da Saúde, 2010)
The author analyzes the deep modifications affecting the exercise of medicine, particularly in assistance to aged people, due to the enormous growth of biomedical technology, a fact that requires an ethical reflection by health professionals. The Cartesian- -Flexenerian model prevailing in medical education introduced variables in health assistance to aged patients that caused dramatic changes in the doctor-patient relationship. The non challenged use of biomedical technology deprived medicine from its characteristics as art, making doctors to not consider the complex dimension of aged patients as biopsychosocial and spiritual characteristics the. The author argues that we need to introduce significant changes in professional training in order to ponder about a humanist model for medicine.